Determining the prospects of the development of the cooperative of fruit and vegetable products - Ergashev Rakhmatulla (E3S Web of Conferences, 2024)
In this article, the economic importance of the fruit-vegetable cooperative and its importance in providing the country's population with food products comes from its relevance. The main goal of the research is to supply industrial enterprises with raw materials by using the system of cooperation in the production of fruit and vegetable products. In the conducted scientific research, the mechanisms of state support for fruit and vegetable growers in the Republic of Uzbekistan, the development trends of fruit and vegetable cooperation in the Kashkadarya region to ensure food safety by improving the fruit and vegetable network as a result of the stable growth of cooperation, and to provide the population with ecologically clean products On the basis of economic-mathematical modeling of directions for determining and improving the efficiency of fruit and vegetable enterprises, forecast parameters until 2026 have been developed.